Unjuk Kerja Filter Pasif dalam Mereduksi Distorsi Gelombang pada AC/DC Konverter - Asnil Asnil (Universitas Negeri Padang, 2020)
This paper shows the use of passive filters to reduce the distortion of input waves in a single phase uncontrolled rectifier. Simulations are carried out with various passive filter models to get a decrease in the value of Total Harmonic Distortion (THD) and correct the distortion of the uncontrolled single phase rectifier input waveform. The results of the simulation show the shape of the input signal changes in the uncontrolled single-phase rectifier, analyzing the value of power factor improvement and also the THD value.